Transformation PAN's Communication Strategy in Attracting Millennial Voter Support for the 2024 Election - Zulfahmi Zulfahmi; Syukur Kholil; Anang Anas Azhar (Faculty of Law, Universitas Pekalongan, 2024)
This study aims to analyze the transformation of the National Mandate Party (PAN) communication strategy in attracting the support of millennial voters in the 2024 Election, with a focus on the effectiveness of the use of digital media and face-to-face interactions. Millennial voters, who dominate up to 56.45% of the total voters, are the main target of PAN's political campaign. This study uses a qualitative descriptive method with the SMCR (Source, Message, Channel, Receiver) analysis framework to explore the main elements in PAN's political communication. Primary data were obtained through in-depth interviews with party members, campaign teams, and millennial voters in North Sumatra, while secondary data were collected from document analysis and PAN's social media content. The results of the study show that PAN has succeeded in attracting the attention of millennial voters through digital campaigns on social media such as Instagram, TikTok, and WhatsApp. However, this digital strategy has not been fully effective in rural areas with limited internet infrastructure. In addition, PAN faces challenges in political regeneration, fierce competition with other parties, and a lack of strong local figures. Inconsistency in delivering messages between the center and regions is also an obstacle in building solid relationships with voters. The study recommends that PAN adopt a hybrid strategy that integrates digital and traditional approaches, strengthens the presence of local figures, and adapts messages to the specific needs of millennial voters. This strategy is expected to increase PAN's political relevance and strengthen its electability in the upcoming election